Analysis of an uncertain volatility model. (19th October 2006) - Di Francesco, Marco; Foschi, Paolo; Pascucci, Andrea
Abstract : We examine, from both analytical and numerical viewpoints, the uncertain volatility model by Hobson-Rogers in the framework of degenerate parabolic PDEs of Kolmogorov type.